MENINGKATKAN KEMAMPUAN PENGUCAPAN KONSONAN GETAR MELALUI METODE MOTOKINESTETIK BAGI ANAK HAMBATAN BICARA - Silfa - Hanum (Universitas Negeri Padang, 2013)
This research is background overshadow from visible problem of field namely the natural child speak in class of III Elementary School number 03 Sungai Angek of subdistrict Baso experiencing of resistance on consonant uttering [r] this matter seen from ability of early child in consonant uttering [r] at word containing consonant [r]. Pursuant to the mentioned hence this research aim to prove effectiveness of method motokinestetic in improving ability of consonant uttering [r] for child speak in class III elementary school number 03 Sungai Angek of subdistrict Baso. The research methodologis is used by single subject research (SSR) with desain A-B-Aand technique analyse data use table and analyse visual data of graph. This subject research is child experiencing speak in class III Elementary school it is variabel measurement by using persentase of how much amount of pregnant word uttering of consonant [r] what is real corrct. Result of analysed to research include cover perception amount of at condition baseline (A1) as much 8 times condition treatment (B) as much 12 times, an condition baseline (A2) as much 5 times result of this research addressed at data analysis in a condition and analyse data usher condition showing existence of change of ability of consonant uttering [r]early word of at child of disparity resistance speak toward better from result of this data acquirement is inferential that method mokinestetic earn used by and effective to increase ability of consonant uttering [r]. Research suggest to parent, teacher and researcher hereinafter in order to earn to use method motokinestetic as one of method to increase the student ability in producing consonant specially consonant [r] and variation on order to the child do not tire of and also it is study is more interesting.